The radio/X-ray domain of black hole X-ray binaries at the lowest radio luminosities - Gallo, E.; Miller-Jones, James; Russell, D.; Jonker, P.; Homan, J.; Plotkin, R.; Markoff, S.; Miller, B.; Corbel, S.; Fender, R. (Oxford University Press, 2014)
We report on deep, coordinated radio and X-ray observations of the black hole X-ray binary XTE J1118+480 in quiescence. The source was observed with the Karl G. Jansky Very Large Array for a total of 17.5 h at 5.3 GHz, yielding a 4.8 ± 1.4 μJy radio source at a position consistent with the binary system. At a distance of 1.7 kpc, this corresponds to an integrated radio luminosity between 4 and 8 × 1025 erg s−1, depending on the spectral index. This is the lowest radio luminosity measured for any accreting black hole to date. Simultaneous observations with the Chandra X-ray Telescope detected XTE J1118+480 at 1.2 × 10−14 erg s−1 cm−2 (1–10 keV), corresponding to an Eddington ratio of ~4 × 10−9 for a 7.5 M☉ black hole. Combining these new measurements with data from the 2005 and 2000 outbursts available in the literature, we find evidence for a relationship of the form lr = α+βlX (where l denotes logarithmic luminosities), with β = 0.72 ± 0.09. XTE J1118+480 is thus the third system – together with GX339-4 and V404 Cyg – for which a tight, non-linear radio/X-ray correlation has been reported over more than 5 dex in lX. Confirming previous results, we find no evidence for a dependence of the correlation normalization of an individual system on orbital parameters, relativistic boosting, reported black hole spin and/or black hole mass. We then perform a clustering and linear regression analysis on what is arguably the most up-to-date collection of coordinated radio and X-ray luminosity measurements from quiescent and hard-state black hole X-ray binaries, including 24 systems. At variance with previous results, a two-cluster description is statistically preferred only for random errors <~0.3 dex in both lr and lX, a level which we argue can be easily reached when the known spectral shape/distance uncertainties and intrinsic variability are accounted for. A linear regression analysis performed on the whole data set returns a best-fitting slope β = 0.61 ± 0.03 and intrinsic scatter σ0 = 0.31 ± 0.03 dex.